Clinical assessment of hypertension in children. Issue 1 (December 2016) - Patel, Nisarg; Walker, Nicole
Abstract The use of blood pressure measurements have become a routine part of physical exam for the evacuation of cardiovascular health adults and, more recently, children. The most widely used definition of hypertension is delineate as greater than 90 % BP according to age, sex, and height by the National High Blood Pressure Education Program. Current research suggests that pediatric hypertension is influenced by multitude of factors including birth weight, maturity during birth, heredity, and diet leading to primary hypertension. Factors influencing secondary hypertension include renal abnormalities, coarctation of the aorta, medications, neoplasm, etc. The treatment for pediatric hypertension is carried out with diet and exercise as the first line of defense. Only under non-compliance with diet and exercise is pharmaceutical intervention appropriate. This paper outlines a concise summary of the current understanding and research for scientists, clinicians, as well as for the general population to better understand pediatric hypertension.